Efficient and Hole‐Transporting‐Layer‐Free CsPbI2Br Planar Heterojunction Perovskite Solar Cells through Rubidium Passivation. Issue 5 (1st March 2019) - Guo, Yixin; Zhao, Fei; Tao, Jiahua; Jiang, Jinchun; Zhang, Jungang; Yang, Jianping; Hu, Zhigao; Chu, Junhao
Abstract: Invited for this month′s cover is the group of Jinchun Jiang at East China Normal University. The image shows a novel inorganic perovskite solar cell with rubidium‐passivated CsPbI2 Br film and a low‐cost carbon electrode. The Full Paper itself is available at 10.1002/cssc.201802690 . Abstract : "Inorganic planar perovskite solar cells were constructed without having to use an expensive and unstable hole‐transportation layer…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201802690 . View the Front Cover here:10.1002/cssc.201900490 .